Chinese Judicial Reform and Legislative Reform: Conflicts and Mutual Promotion - Zhu, Shaoming (Advances in Social Sciences Research Journal, 2024)
In the Chinese law context, judicial reform has close consequences on legislation. On the one hand, some judicial reform outcomes have become laws. On the other hand, when some of the measures and policies of the judicial reform are not consistent with the Constitution and other laws, they could cause problems in practice. This paper argues that judicial reform should be coherent with legislative reform in order to ensure consistency with the Constitution, maintain uniformity in the application of law, and prevent the legislature from exceeding its authority. The purpose of this paper is to consider the legitimacy and limit of the judicial reform power, and search for a balance between efficiency and legitimacy in judicial reform.